Red Blood Cell Shape and Deformability in Patients With COVID-19 Acute Respiratory Distress Syndrome - Piagnerelli, Michaël; Vanderelst, Julie; Rousseau, Alexandre; Monteyne, Daniel; Perez-Morga, David; Biston, Patrick; Zouaoui Boudjeltia, Karim (Frontiers in Physiology, 2022)
Background: Acute respiratory distress syndrome due to COVID-19 is associated with high mortality. Studies have reported that the microcirculation responds adequately to hypoxia in COVID-19 patients by increasing oxygen availability, in contrast to the inadequate response observed in patients with bacterial sepsis. The red blood cells (RBCs) rheology is altered during bacterial sepsis, but few data are available in patients with COVID-19. Methods: Shape was assessed on admission using Pearson’s second coefficient of dissymmetry (PCD) with flow cytometer technique. RBC deformability was determined using ektacytometry by the elongation index. Results were compared across groups. Scanning electronic microscopy was performed on RBCs from COVID-19 patients. RBC shape and deformability were also assessed on days 3 and 7 in COVID-19 patients. Results: 49 ICU patients were included (30 with COVID-19 ARDS and 19 with bacterial sepsis). ARDS was more severe in patients with COVID-19 than in those with sepsis and mechanical ventilation was more frequently required. RBCs were significantly more spherical in septic patients (PCD -0.40 [-0.56; -0.18]) than in healthy volunteers (PCD -0.54 [-0.66; -0.49]) but not than in COVID-19 patients. In COVID-19 non-survivors (n=11), sphericity was more marked on day 7 (PCD -0.40 [-0.47; - 0.28]) than on day 1 PCD vs –0.49 [-0.59; -0.44]); p=0.045. At ICU admission, RBC deformability was altered for all shear stress values studied in septic patients compared to COVID-19 patients and healthy volunteers. In the 18 COVID-19 patients studied for 7 days, RBC deformability did not change over time and was not related to outcome. At day 1, RBCs from COVID-19 patients showed a normal shape on scanning electronic microscopy. Conclusions: In contrast to the significantly altered shape and decreased deformability in patients with bacterial sepsis, RBCs from COVID-19 patients had normal deformability on admission, and this pattern did not change over the first week despite a more spherical shape in non-survivors. As RBCs are the key cell for oxygen transport, this maintenance of normal deformability may contribute to the adequate microcirculatory response to severe hypoxia of the microcirculation that has been observed in these patients.